THE INFLUENCE OF GUIDED INQUIRY LEARNING MODELS ON SOCIAL SKILLS AND LEARNING OUTCOMES OF PPKN CLASS V STUDENTS SD NEGERI 091400 DOLOK SARIBU - Novridah Reanti Purba; Deny Setiawan; Daulat Saragi (SENSEI RESEARCH CENTER, 2023)
This research is motivated by PPKn learning activities still using conventional learning models so that learning is less than optimal. This study aims to determine: (1) how much influence the guided inquiry model has on students' social skills, (2) how much influence the guided inquiry model has on the learning outcomes of ppkn students in grade V of SD Negeri 091400 Dolok Saribu, (3) whether there is an interaction between social skills and ppkn learning outcomes of grade V students of SD Negeri 091400 Dolok Saribu. This research is a quasi-experimental research. The population in this study was all grade IV students of SD Negeri 091400 Dolok Saribu for the 2020/2021 School Year consisting of two classes. The research sample used was all grade IV students of SD Negeri 0901400 using the total sampling sample technique. The instruments used are social skills questionnaires and ppkn class IV learning outcomes tests. The data obtained were then analyzed using ANACOVA and ANAVA in the spss 2 2 program. The results showed that: 1) the magnitude of the influence of the guided inquiry model on the social skills of grade IV students was 0.9 31 or 9 3.1%, 2) the large influence of the guided inquiry model on the learning outcomes of ppkn grade IV students was 0.967 or 9.67%, 3) there was an interaction between the inquiry learning model is guided by social skills and learning outcomes of ppkn grade IV students with a calculated F score of 3,906 so that Ha is accepted and H0 is rejected.